MEMBANGUN KESADARAN ANTI-KORUPSI MELALUI PENDIDIKAN AGAMA ISLAM PADA REMAJA DI SMPN 29 BUTON - Indah Lustian S; Darmayanti; Safaruddin Yahya (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Corruptioniiis a seriousiiproblem facediiby manyiicountries in the world, iincluding Indonesia. iCorruption can damage social and economic systems, hinder development, and weaken public trust. Therefore, preventive efforts with long-term impacts are needed, particularly through education, especially Islamic Religious Education, which instills valuesiisuch as honesty, ijustice, trustworthiness, and responsibility. iThis studyiaims to analyzeithe role of IslamiciReligious Educationiin building anti-corruption awareness among adolescents at SMPN 29 Buton. The methodiused in thisistudy is a descriptiveiqualitative approach, iwith data collection techniquesicarried out throughiobservation, idocumentation, iand interviews with Islamic ReligiousiEducation teachers andistudents as informants. The results of the study indicate that anti-corruption values can be integrated into the learning process of Islamic ReligiousiEducation throughithe cultivation of honesty, responsibility, trustworthiness, and teacher role modeling. In addition, religiousiprograms and character-buildingiactivities atischool can encourage students' awareness of the importance of anti-corruption behavior. Thus, this study emphasizes thatiIslamic ReligiousiEducation hasia significant roleiin building anti-corruption awareness by integrating moral and spiritual values in the learning process.